1989
DOI: 10.1093/oxfordjournals.aje.a115446
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriuria in Representative Population Samples of Persons Aged 72–79 Years

Abstract: Screening for bacteriuria was performed between 1984 and 1988 in persons aged 72-79 years representative of the general population in Göteborg, Sweden. The frequency of bacteriuria (greater than or equal to 10(5)/ml) at a single screening was 6% and 16% at age 72 years and 6% and 14% at age 79 years for the screened men (n = 235 and 259) and women (n = 259 and 297), respectively. By repeated screening after one month and 30 months of those previously negative at age 72 years, an additional 4% and 3% of men and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
10
0
1

Year Published

1991
1991
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 0 publications
4
10
0
1
Order By: Relevance
“…Our prevalence figures for bacteriuria confirm the few previous findings from similar populations [8,10].…”
Section: Comments On Resultssupporting
confidence: 91%
“…Our prevalence figures for bacteriuria confirm the few previous findings from similar populations [8,10].…”
Section: Comments On Resultssupporting
confidence: 91%
“…Several studies have shown that asymptomatic bacteriuria is common (\ 30%) in institutionalized patients. The treatment of this condition does not decrease mortality or morbidity due to other diseases and, moreover, there is a potential risk of an increase in the emergence of resistance (34)(35)(36)(37). This knowledge is probably not widespread, because as many as 60% of GPs chose to treat this patient based only on the history and 60% of these GPs prescribed the antibiotic over the telephone.…”
Section: Discussionmentioning
confidence: 99%
“…Nordestam et al studied a population of elderly patients and compared their longevity in relation to bacteriuria (LoE 1b) [13]. There was no increase in mortality related to bacteriuria for otherwise healthy individuals.…”
Section: Bacteriuria and Mortalitymentioning
confidence: 99%